A Practical Guide to Particle Counting for Drinking Water Treatment - Broadwell, John Michael (CRC Press, 2009)
As EPA standards for water quality have tightened in recent years, the need to more accurately assess filter performance and improve the overall treatment process has led to increased demand for the high sensitivity provided by particle counters. One particle counter can give you more data than a dozen turbidimeters-if you know how to sort through the complexity and confusion.